Complete mitochondrial genome of Hainan partridge, Arborophila ardens (Galliformes: Phasianidae). (August 2014) - Yan, Chaochao; Zhou, Yu; Lu, Lu; Tu, Feiyun; Huang, Ting; Zhang, Xiuyue; Yue, Bisong
Abstract The Hainan partridge, Arborophila ardens belongs to family Phasianidae, and distributes only in Hainan, China. In this study, the complete mitochondrial genome of A. ardens was first sequenced and characterized. The genome is 16, 727 bases in length. Bayesian inference, maximum likelihood and maximum parsimony methods were used to construct phylogenetic trees based on 12 concatenated protein-coding genes located on the heavy strand. Phylogenetic analyses further confirm the Arborophila placed at the root of Phasianidae. Arborophila ardens show closer relationship with A. rufipectus than A. rufogularis and A. gingica which cluster as sister group to A. ardens and A. rufipectus.